Analysis of the Relationship between Knowledge Level and PPI Implementation in the Emergency Room of a Community Health Center - Syahnur, Citra Septiyenri; Lestari, Yuniar; Astiena, Adila Kasni (Journal La Medihealtico, 2025)
Healthcare-associated infections are a global health challenge, not only as a patient safety issue but also as a major driver of antimicrobial resistance. Efforts to prevent and minimize the occurrence of healthcare-associated infections are called infection prevention and control (IPC). The Emergency Department (ED) has the potential for healthcare-associated infections. This study aims to determine the relationship between knowledge levels and the implementation of Infection Prevention and Control (IPC) in the Emergency Department of Community Health Centers in Padang City. This study used a mixed method research method, which combines quantitative and qualitative research types in one research activity with an explanatory sequential design. The population in this study were all healthcare workers working in the Emergency Department of the Padang City Community Health Center, with a sample of 55 people. The study was conducted in February 2024. The results found that 69.1% of respondents were under 46 years old, 96.4% were female, and 72.7% had a D3 educational background. A total of 61.8% had high knowledge. Compliance with PPI implementation was recorded at 38.2%. There is a significant relationship between knowledge and compliance with the implementation of PPI, health workers in the Emergency Department of the Community Health Center with high knowledge are 4.25 times more likely to comply with implementing PPI. Recommendations for improving compliance with PPI implementation are to formulate PPI policies, implement PPI education and training, and strengthen the implementation of monitoring, evaluation, and reporting.